Comparison of pharyngocutaneous fistula closure with and without bacterial cellulose in a rat model. Issue 2 (April 2018) - Demir, Berat; Sarı, Murat; Binnetoglu, Adem; Yumusakhuylu, Ali Cemal; Filinte, Deniz; Tekin, İshak Özel; Bağlam, Tekin; Batman, Abdullah Çağlar
Abstract: Objective: The present study aimed to compare the effects of bacterial cellulose used for closure of pharyngocutaneous fistulae, a complication of total laryngectomy, with those of primary sutures in a rat model. Methods: Thirty female Sprague-Dawley underwent experimental pharyngoesophagotomy and were grouped depending on the material used for pharyngocutaneous fistula closure: group I, which received primary sutures alone, group II, which received bacterial cellulose alone; and group III, which received both. After 7 days, the rats were sacrificed. Pharyngocutaneous fistula development was assessed, the gross wound was inspected, and histological examination was conducted. Results: Pharyngocutaneous fistulae developed in 12 rats (41%) in all: 6 from group I (21%), 4 from group II (14%) and 2 from group III (7%). Conclusion: Fibroblast density and inflammatory cell infiltration were significantly greater in group III than group I. We concluded that bacterial cellulose may be useful for pharyngocutaneous fistula closure.